Guidance for establishing and applying tolerable upper intake levels for vitamins and essential minerals: Draft for internal testing. (24th January 2022) - ,; Turck, Dominique; Bohn, Torsten; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Peláez, Carmen; Pentieva, Kristina; et al.
Abstract: Vitamins and essential minerals are micronutrients that are essential for the normal functioning of the human body. However, they may lead to adverse health effects if consumed in excess. The concept of a tolerable upper intake level (UL) is a science‐based reference value, which was introduced to support policy‐makers and other relevant actors in managing the risks of excess nutrient intake. EFSA's principles for establishing ULs for vitamins and minerals were originally developed by the Scientific Committee on Food in 2000. Since then, experience has been gained and the scientific field developed. This guidance from the EFSA Panel on Nutrition, Novel Foods and Food Allergens provides an updated framework to support EFSA's UL assessments. It covers aspects related to the planning of the risk assessment (problem formulation and definition of methods) and its implementation (evidence retrieval, appraisal, synthesis, integration, uncertainty analysis). As in the previous framework, the general principles developed for the risk assessment of chemicals in food are applied (hazard identification, hazard characterisation, intake assessment, risk characterisation). Peculiar to nutrients are their biochemical and physiological roles and the specific and selective mechanisms that maintain the systemic homoeostasis and body burden of the nutrient. These must be considered when conducting a risk assessment of nutrients. This document constitutes a draft guidance that will be applied in EFSA's assessments during a 1‐year pilot phase and be revised and complemented as necessary. Before finalisation of the guidance, a public consultation will be launched.